Different genotypes and species of symbiotic fungi mediate the behavioral response of invasive Sirex noctilio fabricius (Hymenoptera: Siricidae) - Wang, Ming; Gao, ChengLong; Xu, QinWang; Fu, NingNing; Li, JiaLe; Ren, LiLi; Luo, YouQing (Frontiers in Microbiology, 2024)
In northeast China, the invasive woodwasp., Sirex noctilio, attacks Pinus sylvestris var. mongolica Litv and often shares habitat with native Sirex nitobei. Previous research showed that S. noctilio can utilize the volatiles from its symbiotic fungus (A. areolatum IGS-BD) to locate host trees. Consequently, symbiotic fungi (A. areolatum IGS-D and A. chailletii) carried by S. nitobei may influence the behavioral selection of S. noctilio. This study aimed to investigate the impact of fungal odor sources on S. noctilio’s behavior in laboratory and field experiments. Our observations revealed that female woodwasps exhibited greater attraction toward the fungal volatiles of 14-day-old Amylostereum IGS-D in a “Y”-tube olfactometer and wind tunnel. When woodwasps were released into bolts inoculated separately with three strains in the field, females of S. noctilio exhibited a preference for those bolts pre-inoculated with A. areolatum IGS-BD. Gas chromatography–mass spectrometry (GC–MS) analysis revealed that the volatiles emitted by the two genotypes of A. areolatum were similar yet significantly distinct from those of Ampelopsis chailletii. Hence, we postulate that the existence of native A. areolatum IGS-D could potentially facilitate the colonization of S. noctilio in scenarios with minimal or no A. areolatum IGS-BD present in the host.